Ambiguity in the Quantifiers of the Ethical Propositions in Quran and Hadiths - mohammad alemzadeh noori (اخلاق وحیانی, 2017)
Some of the universal and absolute ethical propositions in the religious sources, despite their universal appearance, have quantifiers with limited scopes. Even there are instances where we know it for certain that the proposition is not universal, but it is apparently absolute or universal. This issue makes us suspicious even about the universality and particularity of other propositions. In the present study, for finding out the real quantifier of these kinds of propositions, we consult the interpretations of Quran and Hadith commentaries, as well as using philosophical and logical analyses. The results show a few possibilities: (1) the propositions are particular, which is against the appearance of the propositions and can be only applied when the proposition has no quantifier, but when there is a quantifier, this possibility is not applicable; (2) relinquishment to the most perfect person, which is dependent on the acceptance of the “relinquishment rule”; (3) the propositions being the expressions of the requirement not the total cause, i.e. considering these propositions in the category of duties, and their universality being due to their nature, not for all cases; (4) particularity after the acceptance of the conventional appearance of these text in absolute or universal forms; (5) predicating on the polarized levels of meaning. The third, fourth and fifth possibilities can be merged. When we know that universal or absolute propositions in religious texts are not always universal and that they may have been restricted or particularized or predicated on different levels of meaning or they are only expressing the requirements and the requirements may have been vanished, our interpretations of religious ethical texts become more accurate and the claims for universality go away. The universal appearance may be due to rhetorical objectives and for recommendation and warning about a certain issue. Even in the cases that the universal quantifiers are explicitly present, we consider the possibility that there can be a rhetorical objective and the correspondent meaning is not intended. Taking the rhetorical intentions into attention may make us free form dogmatic interpretations and claims for universality.